Analysis of Critical Thinking Skills Test Items on The Topic of Temperature, Heat, and Expansion using The Rasch Model - Fibriyana Safitri; Dadi Rusdiana; Achmad Samsudin; Arif Widiyatmoko (PAEDAGOGIA, 2024)
This research aims to analyze the validity, reliability, level of difficulty and differentiating power of critical thinking skills test items, particularly on the topic of temperature, heat, and expansion. The test items consist of eight essay questions which refer to the eight elements of critical thinking according to Inch. The subjects of this research were 31 students in class VIII of junior high school. Before being tested on students, the critical thinking skills test items were evaluated by five experts. The method used to analyze validity, reliability, level of difficulty, and differentiating power of items is the Rasch model using MINISTEP software version 4.3.1. The results of the analysis show that the test items can be used to test students' critical thinking skills on the topic of temperature, heat, and expansion. For future education practice, the test items can be combined with education technology, like flipbooks, to know the development of students' critical thinking skills